Identifikasi Jenis Kerusakan Pada Perkerasan Kaku (Studi Kasus Ruas Jalan Soekarno-Hatta Bandar Lampung) - Sasana Putra; I Wayan Diana; Muhammad Susanto (UNIVERSITAS LAMPUNG, 2016)
Soekarno-Hatta road Bandar Lampung is a network that used the road for the distribution of goods and services (national activities). So that the movement of transportation that there are highly influenced by the condition of pavement that were on the road .Besides , pavement road conditions also impact in smoothness in traffic and the safety and comfort for road users .This research aims to understand the types of damage and value conditions on pavement stiff at soekarno-hatta roads of bandar lampung including maintenance or handling. Methods used to this assessment is pavement condition index (PCI) . Based on the research done, it is known that the rigid pavement on roads Soekarno-Hatta Bandar Lampung are in good condition even excellent with perentase namely : excellent 42,86 %; very good 50 % and good 7,14 %. But types of damage on identified in roads soekarno-hatta lampung when compared spot ( point ) consisting of 16 types of damage : corner break 9,34%; divided slab 3,86%; durability crack 2,81%; faulting 0,51%; joint seal e 10,89%; shoulder drop 1,5%; linier cracking 13,17%; patching large 3,63%; patching small 4,48%; polished aggregate 27,86%; popouts 2,46%; punchout 2,45%; scalling 4,93%; shrinkage 3,39%; spalling corner 3,39%; spalling joint 4,23%. Although in a whole road conditions soekarno-hatta bandar lampung are in good condition even perfect , but routine maintenance on roads and building appendages must be done by period of one year .Routine maintenance the way of covering maintenance the street shoulder , maintenance drainage , routine maintenance for each types of damage , maintenance building appendages roads and others .